Anodal Transcranial Direct Current Stimulation-Induced Effects Over the Right Dorsolateral Prefrontal Cortex: Differences in the Task Types of Task Switching - Wang, Ziyu; Zhu, Rongjuan; You, Xuqun (Frontiers in Psychology, 2021)
Transcranial Direct Current Stimulation (tDCS) has been previously used to investigate the causal relationships between the Dorsolateral Prefrontal Cortex (DLPFC) and task switching but has delivered inconclusive results that may be due to different switching tasks involving different cognitive control processes. In the current study, we manipulated task types and task predictability to investigate the role of DLPFC in task switching performances. Notably, we distinguished the specific effects of anodal-tDCS on two types of tasks (parity/magnitude and parity/vowel-consonant tasks). Forty-eight participants were randomly assigned to four task groups as follows; Group I who was assigned right anode (RA) parity/magnitude tasks, Group II who were assigned sham parity/magnitude tasks, Group III who were assigned RA parity/vowel-consonant tasks, and Group IV who were assigned sham parity/vowel-consonant tasks. Participants were asked to complete both predictable and unpredictable tasks. In the parity/magnitude task, we demonstrated a lower switching cost for the RA group compared to the sham group for unpredictable tasks. In contrast, in the parity/vowel-consonant task, the switching cost was higher for the RA group compared to the sham group for unpredictable and predictable tasks. These findings confirmed an anodal-tDCS induced effect over the right DLPFC both in the parity/magnitude and parity/vowel-consonant tasks. Our data indicated that anodal tDCS over right DLPFC may have the strongest influence task on switching performance by changing the irrelevant task-set inhibition process. Also, the right DLPFC is unlikely to act by performing exogenous adjustment of predictable task switching.